A Novel Secret Sharing Method Based on Binary Sequence - Yexia Cheng; Yuejin Du; Kai Yang; Shen He; Jin Peng; Wen Jiang (Dianxin kexue)
A novel secret sharing method was proposed based on binary sequence,which was quite different from the traditional secret sharing method.This secret sharing method was based on binary secret sequence using bit operations.The secret here included but not limited to key,message,etc,meanwhile the secret sequence included but not limited to key sequence,message sequence and so on.And two new concepts which were called non-M sequence and non-M sequence rule method were defined.By using the non-M sequence rule method,the elements of sub-secret sequence M' of secret sharing were computed.The method for generating sub-secrets and the method for recovering secret was proposed based on binary sequence.The method was practical and effective.